Association between intrinsic capacity trajectories and risk of stroke incidence in middle-aged and older chinese adults: Evidence from a nationwide prospective cohort study based on CHARLS - Sumei Zhou; Min Chen; Shirong Shao; Zhi Zeng (PLoS ONE, 2026)
Background Stroke is a major public health concern and a leading cause of disability and death in aging populations. Intrinsic capacity (IC), a concept introduced by the World Health Organization, reflects an individual's overall functional ability across multiple domains including cognition, psychological well-being, mobility, vitality, and sensory function. IC has emerged as a core metric within the healthy aging framework, but its prospective relationship with stroke risk remains unclear. A deeper understanding of this link may inform early, function-based prevention strategies. Methods This study used data from 10,751 participants aged 45 years or older from the China Health and Retirement Longitudinal Study (CHARLS). Cox proportional hazards models were used to estimate the association between IC and incident stroke, with stepwise adjustment for demographic, behavioral, and health-related covariates. Modeling IC as a continuous variable enabled examination of linear trends, while quartile-based classification allowed evaluation of potential non-linear associations and improved interpretability. Kaplan–Meier curves and log-rank tests were used to compare stroke-free survival across IC quartiles. Restricted cubic spline analysis was performed to explore the presence of a non-linear association between IC and stroke risk. Robustness was tested through sensitivity analyses excluding participants with baseline cognitive impairment and those aged ≥80 years. Statistical analyses were conducted using Stata and R. Results Over a 7-year follow-up, 243 participants (2.26%) experienced incident stroke. Stroke incidence decreased progressively with increasing IC levels, from 4.84% in the lowest quartile to 0.46% in the highest. Kaplan–Meier analysis showed significantly lower cumulative stroke incidence among individuals with higher IC (log-rank p < 0.001). In fully adjusted Cox models, each one-point increase in IC was associated with a 35.1% reduction in stroke risk (HR = 0.649; 95% CI: 0.599–0.702). Compared to the lowest IC quartile, the highest quartile had an 89.6% lower stroke risk (HR = 0.104; 95% CI: 0.055–0.197). Restricted cubic spline models confirmed a predominantly linear inverse association, with a steeper risk gradient at lower IC levels. Subgroup analyses revealed stronger protective associations in women, older adults (≥60 years), urban residents, and non-smokers or non-drinkers. Results remained consistent across all sensitivity analyses. Conclusions Higher IC was independently associated with a significantly reduced risk of incident stroke, underscoring IC's potential as a holistic, function-based indicator of cerebrovascular vulnerability. These findings provide empirical support for the World Health Organization's healthy aging framework, emphasizing IC as a modifiable reserve that reflects early, multidomain functional decline before clinical disease onset. Incorporating IC into routine screening and prevention strategies may enhance early identification of high-risk individuals and enable more targeted, function-oriented interventions, thereby promoting healthy aging and helping to reduce the future burden of stroke.